Laboratory measures of coagulation among trauma patients on NOAs: results of the AAST-MIT. Issue 1 (15th October 2018) - Kobayashi, Leslie M; Brito, Alexandra; Barmparas, Galinos; Bosarge, Patrick; Brown, Carlos V; Bukur, Marko; Carrick, Matthew M; Catalano, Richard D; Holly-Nicolas, Jan; Inaba, Kenji; Kaminski, Stephen; Klein, Amanda L; et al.
Abstract : Background: Warfarin is associated with poor outcomes after trauma, an effect correlated with elevations in the international normalized ratio (INR). In contrast, the novel oral anticoagulants (NOAs) have no validated laboratory measure to quantify coagulopathy. We sought to determine if use of NOAs was associated with elevated activated partial thromboplastin time (aPTT) or INR levels among trauma patients or increased clotting times on thromboelastography (TEG). Methods: This was a post-hoc analysis of a prospective observational study across 16 trauma centers. Patients on dabigatran, rivaroxaban, or apixaban were included. Laboratory data were collected at admission and after reversal. Admission labs were compared between medication groups. Traditional measures of coagulopathy were compared with TEG results using Spearman's rank coefficient for correlation. Labs before and after reversal were also analyzed between medication groups. Results: 182 patients were enrolled between June 2013 and July 2015: 50 on dabigatran, 123 on rivaroxaban, and 34 apixaban. INR values were mildly elevated among patients on dabigatran (median 1.3, IQR 1.1–1.4) and rivaroxaban (median 1.3, IQR 1.1–1.6) compared with apixaban (median 1.1, IQR 1.0–1.2). Patients on dabigatran had slightly higher than normal aPTT values (median 35, IQR 29.8–46.3), whereas those on rivaroxaban and apixaban did not. Fifty patients had TEG results. The median values for R, alpha, MA and lysis were normal for all groups. Prothrombin time (PT) and aPTT had a high correlation in all groups (dabigatran p=0.0005, rivaroxaban p<0.0001, and apixaban p<0.0001). aPTT correlated with the R value on TEG in patients on dabigatran (p=0.0094) and rivaroxaban (p=0.0028) but not apixaban (p=0.2532). Reversal occurred in 14%, 25%, and 18% of dabigatran, rivaroxaban, and apixaban patients, respectively. Both traditional measures of coagulopathy and TEG remained within normal limits after reversal. Discussion: Neither traditional measures of coagulation nor TEG were able to detect coagulopathy in patients on NOAs. Level of evidence: Level IV.